БІОЛОГІЧНІ ПРЕПАРАТИ ДЛЯ ЗАХИСТУ ВІВСА ВІД ХВОРОБ У ПРАВОБЕРЕЖНОМУ ЛІСОСТЕПУ УКРАЇНИ - Ретьман, С. В.; Панченко, Ю. С. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2017)
Species composition of oats diseases in the Right-bank Forest-steppe of Ukraine has been clarified. Results of application of biological fungicides by the method of seed dressing and surface treatment for the protection of tunicate (Chernihivskyi 28 variety) and hull-less (Samuel variety) oats are provided.